The story of Eleanor Roosevelt. - Davidson, Margaret, 1936- (New York, Four Winds Press, 1969)
A biography of the woman who was First Lady during her husband's term as 32d President and who was also a prominent lecturer and writer on sociological and political subjects.
Keywords: Roosevelt, Eleanor, -- 1884-1962 -- Juvenile literature; Presidents' spouses -- United States -- Biography -- Juvenile literature; First ladies; Women -- Biography